GENDER IDENTITY THROUGH THE EKEGUSII NAMING SYSTEM (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper analyses Ekegusii names and how they relate to gender identity. It shows how the naming system is basically based on the premise that a male is socialized to ‘gather wealth’, hence the term omosacha (‘man/husband’), while a female is socialized to ‘take care of (the wealth)’, hence the term omokungu (‘woman/wife’). Thenames that are analysed in this study show the different crafts and activities, such as blacksmiths and herbal dispensers, which malesengaged in traditionally in an effort to gather wealth. With the arrival of the colonizers and missionaries in the in Gusii land (in Kenya), the Abagusii people devised “modern” ways of wealth gathering and ended up with names relating to education, white collar jobs and money. The study also shows that males bear a number of borrowed names, while women bear only one such name. Some of the names given to the females describe their physical features, characteristicsand ornamentation, while others portray them as the carriers of the community’s migration history. Both the males and the females bear names derived from different types of crops and clothes, although theformer bear more of them than the latter. Finally, there are crossgender names borne by both the males and the females, although not in the same proportions. The paper concludes that the assignment of gender-specific names is not arbitrary, as names socially define maleness and femaleness, besides constraining gender behaviour.